A Canadian Working Group Report on Fecal Microbial Therapy: Microbial Ecosystems Therapeutics. (2012) - Allen-Vercoe, Emma; Reid, Gregor; Viner, Norman; Gloor, Gregory B; Hota, Susy; Kim, Peter; Lee, Christine; O'Doherty, Kieran C; Vanner, Stephen J; Weese, J Scott; Petrof, Elaine O
Abstract : A working group from across Canada comprised of clinician and basic scientists, epidemiologists, ethicists, Health Canada regulatory authorities and representatives of major funding agencies (Canadian Institutes of Health Research and the Crohn's and Colitis Foundation of Canada) met to review the current experience with fecal microbial therapy and to identify the key areas of study required to move this field forward. The report highlights the promise of fecal microbial therapy and related synthetic stool therapy (together called 'microbial ecosystems therapeutics') for the treatment of Clostridium difficile colitis and, possibly, other disorders. It identifies pressing clinical issues that need to be addressed as well as social, ethical and regulatory barriers to the use of these important therapies.